PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN LAPTOP MEREK LENOVO DI KOTA PATI - Dian Kris Diyantoro, 13.05.51.0251; Soliha, Euis (Students Journal of Economic and Management, 2016)
The purpose of this study was to analyze the influence of brand image, product quality and perception of prices on consumer purchasing decisions laptop Lenovo brand in Pati. The population in this study is the Lenovo brand laptop users in Pati. The samples in this study using purposive sampling, ie sampling based on certain criteria, namely: those who are older and those who use and have the Lenovo brand laptops. The analytical tool used is multiple linear regression analysis. The results of the analysis can be concluded that in order to know the effect or no effect with positive and score <0,05: Brand image positive effect significant at .520 and 0,000 on consumer purchasing decisions laptop Lenovo brand in Pati. The product quality has positive effect amounting to 0.117 and not significant at 0.087 on consumer purchasing decisions laptop Lenovo brand in Pati. Perception prices positive effect significant at 0.344 and 0,000 on consumer purchasing decisions laptop Lenovo brand in Pati. Keywords : brand image, product quality, price perception and purchasing decisions of consumers